Essential Mathematics and Statisics for Science - Graham Currell (Wiley-Blackwell, 2009)
'Basic Mathematics and Statistics for Science' is a low-level introduction to the essential techniques students need to understand the subject. Little in the way of prior knowledge is assumed, and the approach adopted is a gentle one that leads through examples in the book and website.